A Skills beyond School Review of Switzerland - Fazekas, Mihály (OECD Publishing, 2013)
Higher level vocational education and training (VET) programmes are facing rapid change and intensifying challenges. What type of training is needed to meet the needs of a changing economies? How should the programmes be funded? How should they be linked to academic and university programmes?  How can employers and unions be engaged? This report on Switzerland looks at these and other questions
Keywords: Education; Switzerland